Impact of competitive exercises on the development of defensive skills of junior handball players - Kazem Saleh, Mohamed (SPORT TK-EuroAmerican Journal of Sport Sciences, 2023)
This study aimed at preparing competitive exercises to develop some important skills within the defensive formation of handball, and identifying the impact of competitive exercises on developing defensive skills within the formation used. The researcher used the experimental method, with one-group pretest-posttest design. The sample for the study consisted of 9 handball players from the Iraqi national team for juniors. A set of competitive exercises for both individual and group defensive skills within the defensive formation was prepared to assess successful and failed attempts in pre and post-tests. The researcher utilized the statistical program SPSS to process the data statistically and extract various parameters. The results of the study showed that there is an impact of competitive exercises on the development of defensive handball skills, through the degree of interdependence between players during performance.